Aliterate Consumers' Processing of Drug Risk Information inDirect-to-Consumer Pharmaceutical Advertising. Issue 2 (15th March 2022) - Jae, Haeran; DelVecchio, Devon S.
Abstract: This research investigates how aliterate consumers process drug risk information. An experimental approach and 398 participants were employed to assess the effects of manipulating drug risk presentation format. When drug risk information is presented in paragraph form, highly consumer aliterate individuals display lower levels of drug risk comprehension and different levels of perceived drug risk than their less-consumer aliterate peers. Providing the same information in a bullet format attenuated consumer aliteracy driven differences in comprehension and eliminated differences in perceived drug risk. These results hold important ethical implications regarding how risk information is disclosed in direct-to-consumer pharmaceutical advertising.